Computer aided low noise microwave amplifier design / Syed Badri Sham Syed Abdullah - Syed Abdullah, Syed Badri Sham (1996)
The design objective was to build a low noise amplifier with a gain of 12dB, VSWR less than 2 and noise figure of 3.5dB. The amplifier was to be fabricated on microstrip with a thickness of 0.8mm and a dielectric permittivity of 2.35. This project also aimed to expose the student to the design procedures involved in such application. The amplifier was built from basic, therefore a considerable amount of time was spent on the design procedures, until now known in the industry as a black art. A research grant will be made to enable amplifier fabrication on microstrip and then to analyse its characteristics using scalar or vector analyser. The purpose of this thesis is to present the analysis and design of a low noise microwave amplifier. Microwave techniques have been increasingly adopted in many electronic systems, such as space communications, radar systems and missile electronic systems. As a result of the accelerating growth of microwave technology, research, design and development in institutes and industries, students preparing for and electronics engineers working in the microwave field need to understand the analysis and design of microwave amplifiers for the production of microwave electronic components and systems. In the design of a microwave module or subsystem it is often desirable to interconnect many active and passive elements together.